1913 Mont. Sess. Laws 53, An Act to Provide that Aliens Shall Pay a Gun License, and Providing a Penalty for Failure to Obtain License; to Provide for and Regulate the Duties of the Game and Fish Warden and His Deputies, and to Provide for the Disposition of the Fines so Collected, ch. 38, § 1. - (:unkn) unknown (General Publisher, 1913)
No person not a bona fide citizen of the United States shall own or have in his possession, in the State of Montana, any gun, pistol or other firearm without first having obtained from the Game and Fish Warden a license therefor, which said license shall cost the owner of said firearm the sum of Twenty-five ($25) Dollars, and shall expire one year from date of issuance thereof;
--
Keywords: POSSESSION - DANGEROUS PERSONS